What's hot about otoferlin - Avraham, Karen B (EMBO J, 2016)
Mutations in the otoferlin (OTOF) gene lead to profound hearing loss in humans. Interestingly, a number of missense otoferlin mutations cause hearing defects but only at higher body temperature, and the reasons for this have been elusive until now. A study published in this issue of The EMBO Journal (Strenzke et al, 2016) adds insight into the underlying mechanisms for this heat‐dependent hearing loss.